Forecasting hourly prices in the portuguese power market with ARIMA models - Dias, António Vasconcellos (2010)
Submitted by Bruno Marçal (bruno.marcal@iscte.pt) on 2010-08-26T10:49:38Z No. of bitstreams: 1 Tese Final.pdf: 289190 bytes, checksum: 502db8829f23d796720059bdd402b8e3 (MD5)